Social dialogue in the Public Services in selected ASEAN countries: A comparative overview of the laws, institutions and practices in Indonesia, Malaysia, the Philippines, Singapore and Thailand - Benedicto Ernesto R. Bitonio (International Labour Organization (ILO), 2022)
The study assesses the social dialogue, freedom of association and collective bargaining institutions and practices in the public service among five member-countries of the Association of Southeast Asian Nations (ASEAN), namely Indonesia, Malaysia, the Philippines, Singapore, and Thailand. Generally, "public service" and "public sector" as understood from the Constitutions of the five countries broadly subsume the various branches or agencies of the State performing governmental functions at central and local levels, including State enterprises. The Constitutions of the five countries generally recognize the freedom of association as a fundamental civil liberty, but national legislations typically regulate or restrict trade union rights in the public sector to maintain or protect public order, national security, general welfare or good morals. Malaysia, the Philippines, Singapore and Thailand have their respective institutions and mechanisms that could allow public sector employees, represented by their unions or associations, to engage in some form of social dialogue with their employers, including collective negotiation or bargaining. In public sector social dialogue mechanisms, high-level elected or appointed public administrators responsible for State functions represent the State as employer party. Their unions or organizations represent employees, who come from the civil service or the bureaucracy. Generally, regulation of public sector labour relations makes public sector social dialogue difficult and, in relation to Indonesia, inexistent. The author concludes that there is little evidence to show the meaningful existence of the enabling conditions for effective social dialogue, particularly the existence of strong, independent workers' and employers' organizations as envisioned in fundamental ILO conventions, and of political commitment to engage in social dialogue by all parties.
Keywords: 330; social dialogue; public sector